Evaluación de fungicidas para el control del complejo fungoso Drechslera spp., Phoma spp., Sphacelia sp., Epiccocum spp. (Cerebella spp.) en inflorescencias de Brachiaria brizantha (Panicoideae, Poaceae) - Pineda López, Benjamín; Balcázar, María del Socorro; Rivera, A.L. (2002)
More than 700 accesions of Brachiaria spp. are conserved in small quantities of seeds) in the Germoplasm Bank at CIAT s Genetic Resources Unit (GRU. These have been obtained by donations of other banks, collections of national and international seeds or collected in the sites of origin. As the seed quantities are very low and large quantities of seeds are required for characterization, conservation and distribution, it is indispensable to increase germplasm under field conditions, with the inherent risk of deterioration or loss by the action of pests and pathogens. In order to diminish the effect of these of unfavorable factors, this research was carried out, utilizing fungicides for the control of the fungi Drechslera spp., Phoma spp., Sphacelia. sp., Cerebella spp., identified as the more frequent fungi affecting the Brachiaria spp. inflorescences at the station of Santa Rosa (Popayán, Cauca), where the germplasm is increased. In vitro trials were conducted with Captan, Benomyl, Etrithiadizole+Thiophanate-methyl, Carboxin+Captan, Metallic Copper, Propiconazole, Mancozeb. Clorotalonil, Metalaxil+Mancozeb in three doses. The outputs showed that Propiconazole, Mancozeb and Metalaxil+Mancozeb, were effective against Sphacelia spp., Drechslera spp., Phoma spp. and Epiccocum spp., isolated from seeds of Brachiaria spp. Experiments carried out at the Santa Rosa station, under field conditions , with Propiconazole sprayed periodically on plots cultivated with 72 accesions of B. brizantha, and in several states of inflorescence development, showed effectiveness against Sphacelia sp. when it was sprayed at booting state and in some cases in early flowering. The evaluation of Propiconazole, Mancozeb, and Metalaxil+Mancozeb, applied every two weeks on plots of B. brizantha CIAT number 16322 starting from booting did not show notable differences, may be due at the levels of infection in the plots were very low.